2010
DOI: 10.1117/12.844484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 3D lesion segmentation algorithm on DBT and breast CT images

Abstract: Recently, tomosynthesis (DBT) and CT (BCT) have been developed for breast imaging. Since each modality produces a fundamentally different representation of the breast volume, our goal was to investigate whether a 3D segmentation algorithm for breast masses could be applied to both DBT and breast BCT images. A secondary goal of this study was to investigate a simplified method for comparing manual outlines to a computer segmentation.The seeded mass lesion segmentation algorithm is based on maximizing the radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 7 publications
(5 reference statements)
1
24
0
Order By: Relevance
“…Reiser et al extended it into 3D and showed that it can be applied on dedicated breast CT images [8]. For a given lesion contour dΩ, the 3D RGI is given by:…”
Section: Contour Initializationmentioning
confidence: 99%
See 4 more Smart Citations
“…Reiser et al extended it into 3D and showed that it can be applied on dedicated breast CT images [8]. For a given lesion contour dΩ, the 3D RGI is given by:…”
Section: Contour Initializationmentioning
confidence: 99%
“…In this algorithm, the standard deviation of the Gaussian constraint function was 10 mm, based on Reiser et al's study [8]. Further, to ensure that the initial contour is completely contained within the lesion before the second segmentation stage, morphological erosion is applied to shrink the RGI segmented lesion contour by using the MATLAB function "imerode" with a cubic structuring element.…”
Section: Contour Initializationmentioning
confidence: 99%
See 3 more Smart Citations